2006
DOI: 10.1159/000096351
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases and Atherogenesis in Dependence of Age

Abstract: Background: Changes in the proteoglycan metabolism of the intima of arteries belong to the initial lesions of atherosclerosis (AS). The accumulation of proteoglycans, alterations of pericellular glycoproteins and modulations of collagen turnover also play a fundamental role in the progression of AS. They influence lipid retention, cell behavior and calcinosis. The decisive role played by the matrix metalloproteinases (MMPs) and their inhibiting factors (tissue inhibitors of metalloproteinases [TIMPs]) in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 247 publications
(135 reference statements)
0
15
0
Order By: Relevance
“…18 MMP-1, MMP-2, MMP-3, MMP-7, MMP-8, MMP-9, and MMP-13 are the recently identified macrophages MMPs. 51,[473][474][475][476][477] MMPs are regulated by cytokines and mechanical strain 478 and they exert their effect on the ECM components, including collagen, elastin, and proteoglycans. 51 MMPs are activated and also activate other macrophage proteases especially urokinase (via plasmin).…”
Section: M a C R O P H A G E S I N P L A Q U E R U P T U R E A N D mentioning
confidence: 99%
“…18 MMP-1, MMP-2, MMP-3, MMP-7, MMP-8, MMP-9, and MMP-13 are the recently identified macrophages MMPs. 51,[473][474][475][476][477] MMPs are regulated by cytokines and mechanical strain 478 and they exert their effect on the ECM components, including collagen, elastin, and proteoglycans. 51 MMPs are activated and also activate other macrophage proteases especially urokinase (via plasmin).…”
Section: M a C R O P H A G E S I N P L A Q U E R U P T U R E A N D mentioning
confidence: 99%
“…Genetic polymorphisms may, for example, affect MMP expression levels by conferring protection or propensity to vulnerable plaques [52][53][54]. Moreover, studies using MMP gene knockout mice have indicated that MMP-2 and MMP-9 play key roles in cardiac rupture after myocardial infarction [55,56].…”
Section: Introductionmentioning
confidence: 99%
“…Prognostic significance of circulating MMP-3 for the existence of instable plaques is also of great interest [18] .…”
Section: Introductionmentioning
confidence: 99%